Developing Business Strategy for Indonesian Government Covid-19 Specimen Testing Laboratory through Scenario Planning - Taufiqurrohman, Taufiqurrohman; Putro, Utomo Sarjono (Budapest International Research and Critics University, 2021)
The COVID-19 pandemic is a public health emergency, and COVID-19 specimen testing laboratory plays a critical role in containing the pandemic. This ongoing pandemic has provided an opportunity to assess the preparedness, reaction, and resilience of Indonesia's laboratory systems. Numerous constraints, including population size, geographical fragmentation, staff and equipment distribution, and the uneven capacity of consumables in many areas, have contributed to Indonesia remaining one of the countries with insufficient diagnostic laboratory readiness. The purpose of this study is to navigate the uncertainty of the future by analyzing the potential business impacts of future events and considering alternative possible outcomes for Indonesian government COVID-19 specimen testing laboratory. Four scenarios were developed to serve as a framework for laboratory's strategy due to overcoming obstacles and capitalizing on possibilities over the next five years.25 experts participated in this scenario planning research, including COVID-19 analyst and biomolecular experts from several Covid-19 testing laboratories, health policymakers from various institutions, virologist, researcher and physicians. 19 driving forces identified in this study from a political, economic, social, technological, environmental, and legal perspective that would shape future COVID-19 testing systems and laboratories. Government policy and the emergence of the SARS-CoV2 variant were identified as critical uncertainty variables with the biggest impact and level of uncertainty in the COVID-19 pandemic situation.The implications and options of each scenario are examined, along with recommendations for the Indonesian government and Covid-19 testing laboratories.